Gender equality as a condition and result of increasing the social activity of women - Eleonora Topvoldievna Mirzajonova (Zien Journals, 2022)
As a system of knowledge, gender is a complex of socio-philosophical, sociological, political science, psychological, cultural and other theories that analyze the development of male and female identities and subjectivity, the position of women and men in society, the system of male dominance, the formation of normative relations between “male” and “ feminine" in a particular culture.
Keywords: gender; gender equality; mentality; gender studies